[PP.11.07] THE POLISH REGISTRY FOR FIBROMUSCULAR DYSPLASIA- THE PRELIMINARY REPORT OF CLINICAL FEATURES, SYMPTOMS AND CARDIOVASCULAR COMPLICATIONS IN PATIENTS ENROLLED IN ARCADIA-POL STUDY. (September 2016) - Hanus, K.; Warchol-Celinska, E.; Prejbisz, A.; Florczak, E.; Januszewicz, M.; Michalowska, I.; Jozwik-Plebanek, K.; Miadziolko, M.; Kabat, M.; Peczkowska, M.; Nazarewski, S.; Madej, K.; et al.
Abstract : Objective: To present preliminary evaluation of clinical features, presenting symptoms and cardiovascular complications in patients with fibromuscular dysplasia (FMD) enrolled to ARCADIA-POL registry. Design and method: The first 84 patients with confirmed FMD in any vascular bed were enrolled in ARCADIA-POL registry from 15 Polish sites. Based on Polish-French collaboration ARCADIA-POL registry was instituted in January 2015 to better understand clinical characteristics and management of FMD in Poland, representing region of Central Europe. A standardized FMD data form was used for data collection. All patients underwent detailed clinical evaluation including ambulatory blood pressure monitoring, biochemical evaluation, biobanking, duplex Doppler of carotid and abdominal arteries and whole body angio-CT. Results: We included 84 patients (59F[70.2%], 25M[29.8%], mean age: 42.5 ± 14.8 years, range: 18–72). In the analyzed group FMD was identified most frequently in renal arteries (88.1%). The mean age at the diagnosis of hypertension was 31.7 ± 17.8 years and the FMD was diagnosed on average 5.6 ± 9.5 years later with the mean age at the diagnosis of FMD 38 ± 15.8 years. The most common presenting symptoms of the disease were: hypertension (84.5%), headaches (71.4%), tinnitus (40.5%), dizziness (36.9%) and epigastric (34.5%) or cervical bruits (11.9%). At evaluation 76 patients (90.5%) were found to be hypertensive and were taking a median number of 2 (interquartile range[IR]:1–3) antihypertensive agents. The mean office and 24 h ABPM systolic and diastolic BP values were 131 ± 21/82 ± 13mmHg and 126 ± 16/77 ± 10mmHg, respectively. 41 patients(48.8%) were smokers - 18(21.4%) and 23(27.4%) patients were current and former smokers respectively. Based on questionnaire taken from 84 patients, one patient reported confirmed FMD in her family - 9 members were evaluated and FMD was confirmed in two sisters and father. Among cardiovascular complications reported by patients, cerebrovascular events occurred in 19 patients(22.6%), coronary artery disease in 4 patients(4.8%) and myocardial infarction in 1 patient(1.2%). Conclusions: Preliminary data of ARCADIA-POL registry showed that FMD is occurring primarily in middle-aged women and most frequently in renal arteries. Although a significant proportion of FMD patients may present with a serious cardiovascular complications, many present with nonspecific symptoms and a subsequent delay in the diagnosis.